DOES ENVIRONMENTAL DISCLOSURE OF THE OIL AND GAS INDUSTRY COMPLY WITH THE GRI? EVIDENCE FROM INDONESIA (Journal of Business Management and Accounting, 2023)
The reporting of Corporate Environmental Responsibility (CER) shows the commitment of a company to minimize the negative impacts on the environment caused by its operations. This study attempts to analyze the level of compliance in terms of disclosure in CER reporting by companies operating in the oil and gas industry based on the GRI 300 Environmental Standards reporting guidelines. This study uses content analysis. The data were obtained from relevant documents: the annual and sustainability reports. The data were evaluated using coding techniques. The evaluation results show that Indonesia's oil and gas industry companies exhibit low-compliance in terms of disclosure in their CER reportingand a low compliance level in terms of regulations. Future research could investigate different sectors of the Indonesian economy to further analyze the practice of CER reporting in the country. Future research could also use other data sources for content analysis instead of annual and sustainability reports.